Adaptability and stability of sunflower genotypes in Central Brazil - Grunvald, Anna Karolina; Carvalho, Claudio Guilherme Portela de; Oliveira, Ana Cláudia Barneche de; Andrade, Carlos Alberto de Bastos (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this study was to evaluate the adaptability and stability of sunflower genotype grain and oil yield, in Central Brazil. The analyzed data were obtained from sunflower genotype trials coordinated by Embrapa Soja, from 2004 to 2007. Genotype adaptability and stability were evaluated using the methods of Eberhart & Russell, Porto et al., Rocha et al., and Annicchiarico. The Annicchiarico method divides sites into favorable and unfavorable environments. This method and the one of Porto et al. were similar and more adequate to evaluate genotypic adaptability. For grain yield, the varieties BRSGira 02 and Nutrissol were widely adapted. The hybrids Agrobel 959, MG50 and V03005 and the varieties Catissol and Multissol were adapted to favorable environments and the hybrids BRHS 02 and BRHS 04 were adapted to unfavorable environments. For oil yield, the hybrids Agrobel 959, V03005, MG50, VDH 487, EXP 1441, EXP 1447, and EXP 1446 and the varieties BRSGira 01, BRSGira 02, and Nutrissol were widely adapted. The hybrid MG52 and the varieties Catissol and Multissol were adapted to favorable environments and BRHS 04 and BRHS 02 were adapted to unfavorable environments. The selected genotypes were shown to be stable, but at different levels.